2018
DOI: 10.1007/s00216-018-1164-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical nonenzymatic sensor for cholesterol determination in food

Abstract: The treatment of some inborn metabolism errors requires cholesterol substitution therapy. Cholesterol plays a vital role in the human body. Therefore, the majority of cholesterol determination techniques are targeted to blood and blood serum. Nevertheless, cholesterol determination in food is important as well. In this paper, cholesterol determination using differential pulse voltammetry (DPV) in dairy products (e.g., milk, clotted cream, yogurt, butter, etc.) is reported with a novel nonenzymatic sensor based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Considering the structure of cholesterol and the docking results of host–guest interaction, it can be revealed that the hydrogen bond and hydrophobic interaction were the main driving forces of the 2:1 complex: (1) the hydroxyl group on the A-ring of cholesterol formed the hydrogen bond with the hydroxyl group at the bottom of one HS-β-CD molecule; (2) the strong hydrophobic interactions were constructed between branched chains on the D-ring of the cholesterol and another HS-β-CD. The results showed that cholesterol could be combined with two HS-β-CD molecules so that the HS-β-CD@Au nanostructures were connected together to generate plasmonic hot spots with about a 1.5 nm nanogap (Figure S9), which played an important role in the enhancement of the SERS signal from partially free R6G. , Compared with other reported methods, the dual-mode strategy had a high sensitivity and suitable detection range which could completely satisfy the detection of cholesterol in the human body (Table S1). This indicated that the method of combining FL and SERS based on the synergistic effect of competitive host–guest recognition and FRET improved the analysis performance. …”
Section: Resultsmentioning
confidence: 98%
“…Considering the structure of cholesterol and the docking results of host–guest interaction, it can be revealed that the hydrogen bond and hydrophobic interaction were the main driving forces of the 2:1 complex: (1) the hydroxyl group on the A-ring of cholesterol formed the hydrogen bond with the hydroxyl group at the bottom of one HS-β-CD molecule; (2) the strong hydrophobic interactions were constructed between branched chains on the D-ring of the cholesterol and another HS-β-CD. The results showed that cholesterol could be combined with two HS-β-CD molecules so that the HS-β-CD@Au nanostructures were connected together to generate plasmonic hot spots with about a 1.5 nm nanogap (Figure S9), which played an important role in the enhancement of the SERS signal from partially free R6G. , Compared with other reported methods, the dual-mode strategy had a high sensitivity and suitable detection range which could completely satisfy the detection of cholesterol in the human body (Table S1). This indicated that the method of combining FL and SERS based on the synergistic effect of competitive host–guest recognition and FRET improved the analysis performance. …”
Section: Resultsmentioning
confidence: 98%
“…The cholesterol EGT biosensor showed a wide-linear range up to 60 mM cholesterol concertation from the calibration curve, which is comparatively higher than previous reports (Table I). [34][35][36][37][38][39][40][41][42][43][44] We calculated the sensitivity (37.34 μA mM −1 cm −2 ) of the EGT biosensor from the calibration curve's slope (2.987 μA mM −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Samples were chosen based on their high native sterol concentration [ 15 , 16 ]. Thus, butter and cod-liver oil were chosen for analysing oxidized 3β,3β’-dicholesteryl ethers.…”
Section: Methodsmentioning
confidence: 99%